PENCIPTAAN BUSANA CONVERTIBLE READY TO WEAR DELUXE FOR MALE INSPIRASI RUMAH ADAT SUKU OSING - Anburika, Nudia; Nahari, Inty; Hidayati, Lutfiyah (Style : Journal of Fashion Design, 2025)
The consumptive style of fast fashion products with a short lifespan has a negative impact on environmental pollution due to the large amount of fashion waste. The choice of fast fashion products is driven by consumers desire to appear stylish and constantly seek to stand out.This research is a creation of convertible clothes with alternative style, wich has the following objectives, 1) To describe the idea and concept of creating convertible ready to wear deluxe with the source of the idea traditional house of Osing Tribes, 2) To describe the process of creating fashion, 3) To discribe the final outcomes fashion, and 4) describing the presentation of the fashion. This research uses a project led research creation method through 4 stages among exploration or pre design, design of work, the realization of work, and the desimination of work. The results of this creation are convertible ready to wear deluxe with the source idea traditional house of Osing Tribe. The collection which were presented at two event, one at the grand jury and two at the 35th annual fashion show "JAGAD OSING" 2024 which is received the best of the best appreciation.